2013
DOI: 10.1007/s00408-012-9443-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hyperinflation Correlates with Exertional Oxygen Desaturation in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Routine pulmonary function test results and clinical variables did not correlate with ED in patients with stable COPD. Dynamic hyperinflation strongly correlates with exertional desaturation and could be a reason for this desaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
23
0
2
Order By: Relevance
“…Desaturation during exercise (ED) in COPD can be a predictive factor of mortality (47). The main pathophysiological factors are ventilation-perfusion mismatch and drop of mixed venous oxygen saturation related desaturation during exercise in COPD (47).…”
Section: Correlation Between Desaturation During Exercise and Dynamicmentioning
confidence: 99%
See 2 more Smart Citations
“…Desaturation during exercise (ED) in COPD can be a predictive factor of mortality (47). The main pathophysiological factors are ventilation-perfusion mismatch and drop of mixed venous oxygen saturation related desaturation during exercise in COPD (47).…”
Section: Correlation Between Desaturation During Exercise and Dynamicmentioning
confidence: 99%
“…The main pathophysiological factors are ventilation-perfusion mismatch and drop of mixed venous oxygen saturation related desaturation during exercise in COPD (47). A higher value of diffusion capacity (DLCO) and resting oxygen saturation mostly do not predict desaturation during exercise.…”
Section: Correlation Between Desaturation During Exercise and Dynamicmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, dynamic hyperinflation can be defined as a decline in the IC greater than zero. 20 The cardiovascular response of the exercise was expressed by the following parameters: oxygen pulse (O 2 pulse), V O 2 efficiency slope (OUES), and heart rate recovery (HRR). O 2 pulse (in mL/beats/min) was calculated by dividing instantaneous V O 2 by the heart rate 18 and was recorded at the peak of exercise.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Zafar et al [22] recently found a strong correlation between DH and oxygen desaturation during a 6-min walking test, corroborating the evidence that DH contributes directly to the worsening of COPD signs and symptoms. Other authors have reported that DH-preventive medication improved dyspnea scores and quality of life parameters in patients with COPD [23].…”
Section: Discussionmentioning
confidence: 67%